Frequency of Regular Voluntary Blood Donors and Factors Associated with Blood Donation in Karachi, Pakistan - Rabisa Batool; Nazish Jaffar; Syeda Ramsha Batool; Insia Hasan; Suresh Klanghani; Suresh Kumar; Rubina Ghani (ziauddin University, 2020)
Background: Regular voluntary unpaid blood donation assures safe blood supply in association with minimum infection transmission. The purpose of this study was to identify the frequency of regular voluntary blood donation and to evaluate the causes of donating blood as well as factors impeding blood donations among the medical and nonmedical students of Karachi. Methods: A comparative cross sectional study was conducted among medical and nonmedical students of JSMU and NED University respectively from May to October 2018. Sample size was 272 including 137 medical and 135 non-medical students. Data was analyzed using SPSS version 22.0. Chi-square test of independence/ Fischer's exact test were applied to assess statistical significance. Result: In medical group 5/21(23.8%) voluntary regular donors were recorded. In non-medical group, voluntary regular donors were found to be 8/30 (26.6%) (p>0.00). Medical students most commonly 15/21 (71.4%) donated blood voluntarily in a camp while non-medical participants frequently donated blood as replacement donors 13/30 (43.3%) (p>0.00). Major hindering factor for blood donation in both study groups was non-participation in blood donation derives i.e. 66/116 (56.8%) in medical and 53/105 (50.4%) in non-medical groups respectively. Anemia, 20/116 (17.2%) in medical and 15/105 (14.2%) in nonmedical students was the second major cause of not donating blood. Conclusion: The frequency of regular voluntary blood donations is very low among undergraduates. However, comparatively, the trend is slightly higher among non-medical group. The major hindrance in not donating blood was non-participation in blood donating derives. Conclusion: The frequency of regular voluntary blood donations is very low among undergraduates. However, comparatively, the trend is slightly higher among non-medical group. The major hindrance in not donating blood was non-participation in blood donating derives.